{-# OPTIONS --cubical-compatible --safe #-}
open import Algebra using (Ring)
module Algebra.Properties.Ring {r₁ r₂} (R : Ring r₁ r₂) where
open Ring R
import Algebra.Properties.AbelianGroup as AbelianGroupProperties
open import Function.Base using (_$_)
open import Relation.Binary.Reasoning.Setoid setoid
open import Algebra.Definitions _≈_
open AbelianGroupProperties +-abelianGroup public
renaming
( ε⁻¹≈ε to -0#≈0#
; ∙-cancelˡ to +-cancelˡ
; ∙-cancelʳ to +-cancelʳ
; ∙-cancel to +-cancel
; ⁻¹-involutive to -‿involutive
; ⁻¹-injective to -‿injective
; ⁻¹-anti-homo-∙ to -‿anti-homo-+
; identityˡ-unique to +-identityˡ-unique
; identityʳ-unique to +-identityʳ-unique
; identity-unique to +-identity-unique
; inverseˡ-unique to +-inverseˡ-unique
; inverseʳ-unique to +-inverseʳ-unique
; ⁻¹-∙-comm to -‿+-comm
)
-‿distribˡ-* : ∀ x y → - (x * y) ≈ - x * y
-‿distribˡ-* x y = sym $ begin
- x * y ≈⟨ sym $ +-identityʳ _ ⟩
- x * y + 0# ≈⟨ +-congˡ $ sym (-‿inverseʳ _) ⟩
- x * y + (x * y + - (x * y)) ≈⟨ sym $ +-assoc _ _ _ ⟩
- x * y + x * y + - (x * y) ≈⟨ +-congʳ $ sym (distribʳ _ _ _) ⟩
(- x + x) * y + - (x * y) ≈⟨ +-congʳ $ *-congʳ $ -‿inverseˡ _ ⟩
0# * y + - (x * y) ≈⟨ +-congʳ $ zeroˡ _ ⟩
0# + - (x * y) ≈⟨ +-identityˡ _ ⟩
- (x * y) ∎
-‿distribʳ-* : ∀ x y → - (x * y) ≈ x * - y
-‿distribʳ-* x y = sym $ begin
x * - y ≈⟨ sym $ +-identityˡ _ ⟩
0# + x * - y ≈⟨ +-congʳ $ sym (-‿inverseˡ _) ⟩
- (x * y) + x * y + x * - y ≈⟨ +-assoc _ _ _ ⟩
- (x * y) + (x * y + x * - y) ≈⟨ +-congˡ $ sym (distribˡ _ _ _) ⟩
- (x * y) + x * (y + - y) ≈⟨ +-congˡ $ *-congˡ $ -‿inverseʳ _ ⟩
- (x * y) + x * 0# ≈⟨ +-congˡ $ zeroʳ _ ⟩
- (x * y) + 0# ≈⟨ +-identityʳ _ ⟩
- (x * y) ∎
-1*x≈-x : ∀ x → - 1# * x ≈ - x
-1*x≈-x x = begin
- 1# * x ≈⟨ sym (-‿distribˡ-* 1# x ) ⟩
- (1# * x) ≈⟨ -‿cong ( *-identityˡ x ) ⟩
- x ∎
x+x≈x⇒x≈0 : ∀ x → x + x ≈ x → x ≈ 0#
x+x≈x⇒x≈0 x eq = +-identityˡ-unique x x eq
x[y-z]≈xy-xz : ∀ x y z → x * (y - z) ≈ x * y - x * z
x[y-z]≈xy-xz x y z = begin
x * (y - z) ≈⟨ distribˡ x y (- z) ⟩
x * y + x * - z ≈⟨ +-congˡ (sym (-‿distribʳ-* x z)) ⟩
x * y - x * z ∎
[y-z]x≈yx-zx : ∀ x y z → (y - z) * x ≈ (y * x) - (z * x)
[y-z]x≈yx-zx x y z = begin
(y - z) * x ≈⟨ distribʳ x y (- z) ⟩
y * x + - z * x ≈⟨ +-congˡ (sym (-‿distribˡ-* z x)) ⟩
y * x - z * x ∎